Effects of herbivory and its timing on reproductive success of a tropical deciduous tree. (15th August 2020) - Quiroz-Pacheco, Enya N; Mora, Francisco; Boege, Karina; Domínguez, César A; del-Val, Ek
Abstract: Background and Aims: The implications of herbivory for plant reproduction have been widely studied; however, the relationship of defoliation and reproductive success is not linear, as there are many interacting factors that may influence reproductive responses to herbivore damage. In this study we aimed to disentangle how the timing of foliar damage impacts both male and female components of fitness, and to assess when it has greater impacts on plant reproductive success. Methods: We measured herbivore damage and its effects on floral production, male and female floral attributes as well as fruit yield in three different phenological phases of Casearia nitida (Salicaceae) over the course of two consecutive years. Then we tested two models of multiple causal links among herbivory and reproductive success using piecewise structural equation models. Key Results: The effects of leaf damage differed between reproductive seasons and between male and female components of fitness. Moreover, the impact of herbivory extended beyond the year when it was exerted. The previous season's cumulated foliar damage had the largest impact on reproductive characters, in particular a negative effect on the numbers of inflorescences, flowers and pollen grains, indirectly affecting the numbers of infructescences and fruits, and a positive one on the amount of foliar damage during flowering. Conclusions: For perennial and proleptic species, the dynamics of resource acquisition and allocation patterns for reproduction promote and extend the effects of herbivore damage to longer periods than a single reproductive event and growing season, through the interactions among different components of female and male fitness.